Manajemen Pelatihan TI dalam Meningkatkan Kesiapan Siswa SD Menghadapi ANBK - Arianti, Vera Desi; Warta, Waska (Jayapangus Press, 2025)
Digital transformation in education requires students to be prepared for technology-based assessments, such as the National Computer-Based Assessment (ANBK). This study aims to analyse information technology (IT) training management in improving the readiness of fifth-grade elementary school students to face the ANBK, with case studies at SDN Muhara and SDN Sayangsemper in Cianjur Regency. The approach used is qualitative with a case study method, focusing on Henry Fayol's five management functions: planning, organising, directing, coordinating, and controlling. Data were collected through participatory observation, in-depth interviews, and documentation of the training programme. The results of the study indicate that despite the limited facilities available at both schools, the implementation of structured and collaborative training management successfully improved students' skills in using IT devices. Adaptive planning, a simple yet functional organisational structure, contextual direction, intensive coordination, and collaborative supervision were proven to be effective. This training not only improved technical skills but also fostered responsible digital citizenship. The study concludes that well-designed IT training management can strengthen primary school students' digital readiness and serve as a model for implementation in other schools.